O comportamento de compra do consumidor no contexto da saúde mental e o impacto dos meios de pagamento - Lazzaretti, Kelli Laura (2025)
Consumption goes beyond the simple acquisition of goods and assumes psychological and social functions. Compulsive behavior, characterized by a lack of control over consumption, affects an individual's emotional health, social relationships, and financial stability. The general objective of this article is to analyze the impact of payment methods and mental health aspects on compulsive buying behavior in Brazilian adults. This applied, descriptive-level study with a quantitative approach conducted a survey using non-probabilistic convenience sampling. The research instrument, made available electronically through social media, collected socioeconomic information and included two validated scales: the Richmond Compulsive Buying Scale (RCBS) and the Scale of Attitudes Toward Debt. The sample consisted of 241 participants from different regions of Brazil. The results showed that 10.8% of participants exhibited traits compatible with compulsive buying, particularly among women, individuals without children, those with incomplete higher education, with a personal income between one and two minimum wages, dependent on family income, diagnosed with anxiety, and who frequently use payment methods that reduce spending awareness. The study concludes that both emotional factors and ease of payment contribute to the development of this behavior, highlighting the need to focus on mental health and financial education as preventive strategies.